Wildlife Study Design - Morrison, Michael L.; Block, William M.; Strickland, M. Dale.; Collier, Bret A.; Peterson, Markus J.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2008)
After the success of the first edition, Wildlife Study Design returns with a second edition showcasing a substantial body of new material applicable to the study design of ecology, conservation and management of wildlife. Building on reviews of the first edition and feedback from workshops and graduate teaching, this new edition, authored by Michael Morrison, William Block, M. Dale Strickland, Bret Collier, and Markus Peterson, proves to be a valuable guide and reference for scientists and resource managers, as well as being a useful textbook for advanced undergraduate and graduate students. Taking an approach from both a basic and applied perspective, the book covers numerous aspects of study design including variable classification, the necessity of randomization and replication in wildlife study design, the three major types of designs in decreasing order of rigor, detection probabilities, adaptive cluster methods, double sampling, sampling of rare species, effect size and power, and impact assessment, just to name a few. The concepts provided by the book make study design both accessible and comprehensive to a wide array of readers.
Concepts for Wildlife Science: Theory -- Concepts for Wildlife Science: Design Application -- Experimental Designs -- Sample Survey Strategies -- Sampling Strategies: Applications -- Impact Assessment -- Inventory and Monitoring Studies -- Design Applications -- Education in Study Design and Statistics for Students and Professionals -- Synthesis: Advances in Wildlife Study Design.
Keywords: Animal ecology; Wildlife; Fish; Applied ecology; Environmental management; Environmental sciences; Nature conservation; Animal Ecology; Fish & Wildlife Biology & Management; Applied Ecology; Environmental Management; Math. Appl. in Environmental Science; Nature Conservation